Tinjauan Model Pembelajaran oleh Orang Tua Pada Masa Pandemi Covid 19 dalam Perspektif Pendidikan Islam - Erliana Erliana; Risdoyok Risdoyok (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
The dynamics of the learning process felt by parents during home learning, many parents find it difficult to provide guidance, direct or explain materials that their children do not understand. On the other hand, all this time, parents have been comfortable leaving their children in educational institutions, all of them submitting the entirety of their children's education issues to schools. The purpose of this study was to find out and obtain data about the learning model by parents during the COVID-19 pandemic based on an Islamic perspective. This type of research is "library research" by describing the data that has been collected, then selecting and processing the necessary data according to the discussion in the study. The results showed that the habituation model carried out by parents in guiding children during the covid-19 pandemic was (a) making schedules and rules together, (b) activity ideas, (c) Positive communication, (d) reminding time and introspection, (e) reflection and relation.